Positive correlation between insulin resistance and iron overload-induced oxidative stress in patients with fanconi anemia (FA)- and non-FA-related bone marrow failure: The results of a multicenter study. (2nd January 2016) - Erduran, Erol; Bahadir, Aysenur; Albayrak, Davut; Aliyazicioglu, Yuksel; Buyukavci, Mustafa; Turan, Ibrahim
Abstract: This study investigated the relationship between DNA, protein, and lipid oxidations and insulin resistance in patients with Fanconi anemia (FA)- and non-FA-related bone marrow failure. Sixteen patients with FA, 7 non–FA-related aplastic anemia, and 10 controls were included in the study. Fasting blood glucose, simultaneous insulin, hepcidin, ferritin, 8-hydroxy deoxyguanosine (8-OHdG), protein carbonyls, malondialdehyde (MDA), and homeostatic model assessment–insulin resistance (HOMA-IR) were investigated in the patients and controls. Diepoxybutane test–positive (DEB+) patients were diagnosed with FA, whereas DEB-patients were diagnosed as non-FA. 8-OHdG levels in both FA and non-FA patients were significantly higher than those in the controls ( P = .001 and P = .005, respectively). Serum ferritin levels were also higher in FA and non-FA patients than in the controls ( P = .0001 and P = .005, respectively). Insulin resistance (IR) was significantly higher in FA patients than in non-FA patients and controls ( P = .005 and P = .015, respectively). Significant differences were observed between 8-OHdG, ferritin, and MDA levels in patients with or without IR ( P = .009, P = .001, and P = .013, respectively). Moderate and strong relations of 44% and 85% were determined between IR and ferritin levels in patients with FA or non-FA ( P = .08 and P = .014, respectively). FA and non-FA patients exhibited a tendency to IR. IR was related to ferritin levels, and ferritin levels were also correlated with oxidative stress. These findings suggest that the increased rate of IR in patients with FA and non-FA may derive from increased oxidative stress, which may in turn be due to elevated serum ferritin levels.